The presse pourri and the debate on the French Popular Front’s press Law - Rodríguez Infiesta, Víctor (Historia y Política, 2022)
In December 1936, a debate was held in the House of Deputies on the French Popular Front’s draft press law, followed a few months later by a debate in the Senate House. At the time, a parallel debate to the one in the National Assembly took place in various places both beforehand and afterwards. This was a time when interest was raging in the key issue of the role of journalism in a democratic society, such as the influence of economic power on an information system. This controversy, which has probably not been given the value it deserves, arose at a political moment to which it partly owes its importance. In addition, it took place after people had aired their concerns at the venality of journalism and the impact of money on the press. This paper uses numerous printed sources to tackle the main approaches that had been taking shape from the late 1920s on, especially within the left, until it materialised in a failed, but definitely not trivial, draft law. The major question that was passionately discussed at the time goes far beyond a historical moment or a specific country: can one speak of democracy if public opinion and its channels of expression appear systematically distorted in favour of individual interests or a minority with extraordinary resources?
Keywords: France; press; Popular Front; economic power; 1930s